2000
DOI: 10.1523/jneurosci.20-22-08435.2000
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-I Promotes Neurogenesis and Synaptogenesis in the Hippocampal Dentate Gyrus during Postnatal Development

Abstract: The in vivo actions of insulin-like growth factor-I (IGF-I) on the growth and development of the hippocampal dentate gyrus were investigated in transgenic mice that overexpress IGF-I postnatally in the brain and in normal nontransgenic littermate controls. Stereological analyses of the dentate gyrus were performed by light and electron microscopy on days 7, 14, 21, 28, 35, and 130 to determine postnatal changes in the numerical density and total number of neurons and synapses. The volumes of both the granule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
220
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 325 publications
(230 citation statements)
references
References 61 publications
7
220
0
3
Order By: Relevance
“…With respect to IGF-1, a number of studies have shown that circulating levels of IGF-1 stimulate proliferation (Aberg et al, 2000;Trejo et al, 2001). In addition, IGF-1 overexpression promotes neurogenesis and synaptogenesis in the dentate gyrus and IGF-1 knock out mouse exhibit a reduction in granule cell numbers (Beck et al, 1995;O'Kusky et al, 2000). Furthermore, Ziv et al (2006) reported that environmental enrichment-induced neurogenesis in the hilus correlates with hilar microglial activation and IGF-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to IGF-1, a number of studies have shown that circulating levels of IGF-1 stimulate proliferation (Aberg et al, 2000;Trejo et al, 2001). In addition, IGF-1 overexpression promotes neurogenesis and synaptogenesis in the dentate gyrus and IGF-1 knock out mouse exhibit a reduction in granule cell numbers (Beck et al, 1995;O'Kusky et al, 2000). Furthermore, Ziv et al (2006) reported that environmental enrichment-induced neurogenesis in the hilus correlates with hilar microglial activation and IGF-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Given that insulin and insulin-like factors not only protect brain tissue, but also favor processes such as neurogenesis and synaptogenesis (O'Kusky et al, 2000;van der Heide et al, 2005), and on the background of reduced CNS expression of genes encoding insulin and related messengers in patients suffering from AD (Steen et al, 2005), this outcome may be of considerable relevance for future clinical applications of insulin compounds in the treatment of memory disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In young animals, systemic administration of IGF-1 decreases lesion-induced motor neurone cell death and promotes muscle re-innervation (Vergani et al, 1998). IGF-1 also promotes neurogenesis and synaptogenesis in diverse areas of the central nervous system such as the hypocampal dentate gyrus during postnatal development (O'Kusky et al, 2000) or increases proliferation of granule cell progenitors (Ye et al, 1996). These studies suggest that IGF-1 might have beneficial effects on spinal cord motor neurones from senescent mammals.…”
Section: Effects Of Igf-1 On Neuronesmentioning
confidence: 96%